2014
DOI: 10.1180/minmag.2014.078.6.02
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the solvent-mediated transformation of hydromagnesite into magnesite at different temperatures

Abstract: The process of transforming hydromagnesite to magnesite is analysed in the context of the theory of solvent-mediated transformations. A series of experiments at 120, 150 and 180ºC with different heating times was designed to determine, by powder X-ray diffraction, the amount of magnesite generated as a function of time. The aqueous-phase composition was monitored by inductively coupled plasma-mass spectrometry and carbonate alkalimetry. From the analytical data, the evolution of saturation indexes with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…For simplicity, we thus consider hydromagnesite as the most likely precursor to magnesite. The transformation of hydromagnesite into magnesite can occur either via (thermal) dehydration (Hollingberry and Hull, 2010;Zhang et al, 2000) or dissolution/re-precipitation (Di Lorenzo et al, 2014;Königsberger et al, 1999;Zhang et al, 2000), with the latter inducing an additional Mg-isotope fractionation step with Δ 26 Mghmgs-fluid ~ -1.0 ‰ (Shirokova et al, 2013) in the formation pathway of low temperature magnesite.…”
Section: Mg Isotope Fractionation During Precipitationmentioning
confidence: 99%
“…For simplicity, we thus consider hydromagnesite as the most likely precursor to magnesite. The transformation of hydromagnesite into magnesite can occur either via (thermal) dehydration (Hollingberry and Hull, 2010;Zhang et al, 2000) or dissolution/re-precipitation (Di Lorenzo et al, 2014;Königsberger et al, 1999;Zhang et al, 2000), with the latter inducing an additional Mg-isotope fractionation step with Δ 26 Mghmgs-fluid ~ -1.0 ‰ (Shirokova et al, 2013) in the formation pathway of low temperature magnesite.…”
Section: Mg Isotope Fractionation During Precipitationmentioning
confidence: 99%
“…The scenario is different if the process considered is the precipitation from aqueous constituents instead of a transformation reaction. The solid formed during the precipitation is enriched in Pb if compared with the initial stoichiometry of the solutions, which are characterized by a low abundance of Pb relative to Mg. MGS formation at room temperature is kinetically hindered [12,[48][49][50]. Instead, metastable hydrated Mg-bearing carbonates are formed [51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Anhydrous magnesium carbonate, magnesite, has a rhombohedral structure, thus it should be less prone to suffer surface passivation by cerussite. However, magnesite (MGS) is renowned for the slow dissolution and growth kinetics at room temperature conditions in the framework of the so-called dolomite problem [11][12][13]. The reasons underlying this behaviour have been assigned to two peculiar characteristics of this mineral: (i) the lattice limitation in the spatial configuration of the carbonate unit in the crystalline structure [14,15]; (ii) the low polarizability of Mg 2+ that leads to a high hydration energy and an elevated residence time of water molecules in the first hydration shell [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Montes-Hernandez, Renard, Chiriac, Findling and Toche [39] previously showed that the duration of this phase transformation at moderate pressure and temperatures below 150 °C is in the order of days. Di Lorenzo, Rodriguez-Galan and Prieto [40] has also reported phase transformation at considerably lower pressure although temperature was demonstrated to be a key variable with times of transformation also extending to many days at temperature of 120 °C [40].…”
Section: Discussionmentioning
confidence: 99%